Genetic and molecular mechanism for distinct clinical phenotypes conveyed by allelic truncating mutations implicated in FBN1. Issue 1 (27th November 2019) - Lin, Mao; Liu, Zhenlei; Liu, Gang; Zhao, Sen; Li, Chao; Chen, Weisheng; Coban Akdemir, Zeynep; Lin, Jiachen; Song, Xiaofei; Wang, Shengru; Xu, Qiming; Zhao, Yanxue; et al.
Abstract: Background: The molecular and genetic mechanisms by which different single nucleotide variant alleles in specific genes, or at the same genetic locus, cause distinct disease phenotypes often remain unclear. Allelic truncating mutations of FBN1 could cause either classical Marfan syndrome (MFS) or a more complicated phenotype associated with Marfanoid–progeroid–lipodystrophy syndrome (MPLS). Methods: We investigated a small cohort, encompassing two classical MFS and one MPLS subjects from China, whose clinical presentation included scoliosis potentially requiring surgical intervention. Targeted next generation sequencing was performed on all the participants. We analyzed the molecular diagnosis, clinical features, and the potential molecular mechanism involved in the MPLS subject in our cohort. Results: We report a novel de novo FBN1 mutation for the first Chinese subject with MPLS, a more complicated fibrillinopathy, and two subjects with more classical MFS. We further predict that the MPLS truncating mutation, and others previously reported, is prone to escape the nonsense‐mediated decay (NMD), while MFS mutations are predicted to be subjected to NMD. Also, the MPLS mutation occurs within the glucogenic hormone asprosin domain of FBN1. In vitro experiments showed that the single MPLS mutation p.Glu2759Cysfs*9 appears to perturb proper FBN1 protein aggregation as compared with the classical MFS mutation p.Tyr2596Thrfs*86. Both mutations appear to upregulate SMAD2 phosphorylation in vitro. Conclusion: We provide direct evidence that a dominant‐negative interaction of FBN1 potentially explains the complex MPLS phenotypes through genetic and functional analysis. Our study expands the mutation spectrum of FBN1 and highlights the potential molecular mechanism for MPLS. Abstract : In the present report, we provide genetic and functional evidence for potential dominant‐negative alleles in MPLS patients caused by truncating FBN1 variants escaping NMD. These genetic and functional investigations also include description of the first patient with MPLS of Chinese ancestry.